Evaluation of Staphylococcal Enterotoxins Genes Exposure by Consumption of Ready-to-Drink Milk Products in Mbeya, Tanzania - Heriel Fanuel Massawe; Sharadhuli Iddi Kimera; Robinson Hammerthon Mdegela; Lusato Revocatus Kurwijila (Agricultural Sciences: Techniques and Innovations Vol. 2, 2025)
Staphylococcus aureus is a well-known pathogenic microorganism most frequently linked with foodborne diseases. This study assessed the exposure of humans to Staphylococcus species expressing the Enterotoxin genes (SEs) through consumption of boiled-milk-served-hot and fermented milk in Mbeya, Tanzania. The study was carried out in the Mbeya and Mbozi districts in the Mbeya region, which have a high population of dairy cattle. Two questionnaires were administered to firstly milk consumers who were in the milk shop at the time of visits and willing to participate and secondly, milk shop owners to record information on the quality procedure followed when receiving milk. The sampling of milk (raw, boiled-milk-served-hot and fermented milk) was carried out concurrently with administering the questionnaire. A laboratory analysis was performed where the isolation of S. aureus was performed using a standard procedure, and finally, the detection of SEs genes in the milk was determined. A stochastic model was developed for the exposure to the SEs genes by consumers of boiled-milk-served-hot and fermented milk. The survey involving 120 consumers revealed that 67.5% of the respondents were buying raw milk from milk shops for home consumption. About 76% of respondents boiled milk before consumption, 14.8% fermented the milk after boiling, and 5.8% consumed fermented milk without boiling. Children (30%) consumed milk more frequently than other members of the family. Among consumers, 71% were daily consumers of both boiled-milk-served-hot and fermented milk. Approximately 1197 L (90% CI, 987-1416) of ready-to-consume milk was sold per day. Of which 860 L (90% CI, 645-1071) and 337 L (90% CI, 168-530) were boiled-milk-served-hot and fermented milk, respectively. Out of the ready-to-consume milk, 490 L (90% CI, 464-516) of boiled-milk-served-hot was contaminated with SEs genes compared to 77.5 L (90% CI, 67-88) of fermented milk. Daily, 2394 people were consumers of milk and their products. Exposure assessment shows that the probability of consuming boiled-milk-served-hot and fermented milk contaminated with SEs gene at a milk shop was 0.42 (90% CI, 0.071-0.838) and 0.17 (90% CI, 0-0.62), respectively. It was estimated that every day, 363 (90% CI, 341-385) and 58 (90% CI, 49-66) people were likely to consume boiled milk taken hot and fermented milk contaminated with SE gene, respectively. Odd ratio analysis showed that the exposure to SE gene was two times more likely to occur in people who consume boiled-milk-served-hot milk (P < 0.05) (OR: 2.21 (90% CI, 0.6-6.16) than in people who consume fermented milk. Hygiene training needs to be implemented to reduce the contamination of SEs on the ready-to-consume milk is recommended. Awareness creation on proper food handling among milk handlers to reduce contamination along the milk value chain is recommended.